Cost-Utility Analysis of Community Case Management for Malaria Control in Burundi - Nina Hezagira; Sitaporn Youngkong; Arthorn Riewpaiboon (Kerman University of Medical Sciences, 2022)
Background  The community case management (CCM) program for malaria control is a community-based strategy implemented to regulate malaria in children in Burundi. This study compared the cost and utility of implementing the CCM program combined with health facility management (HFM) versus HFM alone for malaria control in children under five in Burundi.Methods  This study constructed a five-year Markov model with one-week cycles to estimate cost-utility and budget impact analysis (BIA). The model defined 10 health states, simulating the progression of the disease and the risk of recurrent malaria in children under five years of age. Cost data were empirically collected and presented for 2019. Incremental cost per disability-adjusted life year (DALY) averted, and a five-year budget was estimated. One-way and probabilistic sensitivity analyses (PSAs) were then performed.Results  From provider and societal perspectives, combining the CCM program with HFM for malaria control in Burundi was more cost-effective than implementing HFM alone. The addition of CCM, using artesunate amodiaquine (ASAQ) as the first-line treatment, increased by US$1.70, and US$ 1.67 per DALY averted from the provider and societal perspectives, respectively. Using Artemether Lumefantrine (AL) as the first-line treatment, adding the CCM program to HFM increased by US$ 1.92, and US$ 1.87 per DALY averted from the provider and societal perspectives. At a willingness-to-pay of one GDP/capita, the CCM program remained a 100% chance of being cost-effective. In addition, implementing the program for five years requires a budget of US$ 15 800 486-19 765 117.Conclusion  Implementing the CCM program and HFM is value for money for malaria control in Burundi. The findings can support decision-makers in Burundi in deciding on resource allocation, especially during the program's scale up.